2019
DOI: 10.1049/iet-wss.2018.5114
|View full text |Cite
|
Sign up to set email alerts
|

Non‐zero‐sum game‐based trust model to enhance wireless sensor networks security for IoT applications

Abstract: Nowadays, trust models of wireless sensor networks (WSNs) security have flourished due to the day-today attack challenges, which are most popular for internet of things (IoT). This article proposes a trust model based on non-zero-sum game approach for clustered-WSNs (CWSNs) security to maximise the data trustworthiness transmission. The proposed model is developed for two different attack-defence scenarios. In the first scenario, the trust model is used to face a denial-of-service (DoS) attack in which the att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Coordination game has been used in Reference 71 for trust modeling in multihop networks. Trust modeling‐based on nonzero‐sum game approach is done in Reference 72 to provide security against denial of service (DoS) attack and ON‐OFF attack to maximize the data trustworthiness in transmission.…”
Section: Background Work and Motivationmentioning
confidence: 99%
“…Coordination game has been used in Reference 71 for trust modeling in multihop networks. Trust modeling‐based on nonzero‐sum game approach is done in Reference 72 to provide security against denial of service (DoS) attack and ON‐OFF attack to maximize the data trustworthiness in transmission.…”
Section: Background Work and Motivationmentioning
confidence: 99%
“…In this section, we briefly describe our research work from three aspects: The application of game theory, the application of trust, and the application of joint game theory and trust; and give some examples in the literature. Through the investigation of literature, we have concluded that most researchers use the following types of games: Dynamic game [32][33][34][35][36][37][38][39][40][41][42][43][44][45], static game [46], non-cooperative game [47][48][49][50][51], cooperative game [52][53][54][55][56][57][58][59], security game [60][61][62][63][64], and trust game [65][66][67][68][69].…”
Section: Relate Summarized Workmentioning
confidence: 99%
“…In this literature, researchers use trust relationships, trustworthiness, and other factors for decision-making. Based on trust, the researchers proposed some trust models [34,40,49,52,53,58,59,64,69,75,79], trust mechanisms [32,42,43,78,82], and trust frameworks [57]. They provide a better selection scheme for players in the network/system through trust evaluation.…”
Section: Relate Summarized Workmentioning
confidence: 99%
“…The uncontrolled WSNs security is a double defect: one is data deterioration and second is losing power consumption in transmission of designated infected data. Consequently, security in WSNs-based CR is a prominent issue that has been considered in [8,[17][18][19][20][21].One of the eminent techniques utilized in the literature to handle the security problem in WSNs is game theory [22][23][24][25][26]. Game theory is a special optimization branch which tackles the interaction among a set of rational intelligent users that aim to enhance their individual gains in an intelligent and adaptive way [27].…”
mentioning
confidence: 99%
“…One of the eminent techniques utilized in the literature to handle the security problem in WSNs is game theory [22][23][24][25][26]. Game theory is a special optimization branch which tackles the interaction among a set of rational intelligent users that aim to enhance their individual gains in an intelligent and adaptive way [27].…”
mentioning
confidence: 99%